2017
DOI: 10.3390/ma10010087
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution in High Purity Aluminum Single Crystal Processed by Equal Channel Angular Pressing (ECAP)

Abstract: Aluminum single crystal with 99.999% purity was deformed at room temperature by equal channel angular pressing (ECAP) up to 16 passes. Grain size and misorientation of processed samples were quantitatively characterized by TEM and EBSD. The results show that the refinement efficiency of high purity aluminum single crystal was poor in the initial stage. Extrusion by fewer ECAP passes (n ≤ 8) resulted in only elongated grains containing a large number of subgrains and small misorientations between grains. Stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Severe plastic deformation (SPD) techniques have been extensively reported to effectively enhance the mechanical properties of metallic materials [17,18,19,20,21]. For instance, excellent tensile properties (including high yield or ultimate stress and elongation), as well as extremely high impact toughness, can be obtained in Al alloys using equal-channel angular pressing (ECAP), especially via the multipass ECAP process [22,23]. The primary reason for the remarkable improvement in mechanical properties by ECAP processing is the effective microstructure refinement induced by imposed severe strain, which offers significant strengthening via grain boundary strengthening [24].…”
Section: Introductionmentioning
confidence: 99%
“…Severe plastic deformation (SPD) techniques have been extensively reported to effectively enhance the mechanical properties of metallic materials [17,18,19,20,21]. For instance, excellent tensile properties (including high yield or ultimate stress and elongation), as well as extremely high impact toughness, can be obtained in Al alloys using equal-channel angular pressing (ECAP), especially via the multipass ECAP process [22,23]. The primary reason for the remarkable improvement in mechanical properties by ECAP processing is the effective microstructure refinement induced by imposed severe strain, which offers significant strengthening via grain boundary strengthening [24].…”
Section: Introductionmentioning
confidence: 99%
“…For both ECAP and HPT, the saturation of grain size occurs whenever there is a balance between the formation of dislocation structure and its recovery [37,45,46]. Moreover, for both ECAP and HPT, the evolution of the grain size with the strain follows the same trend: at lower stains, the grain size is rapidly decreased with increasing the strain, then it slows down and finally remains constant with further straining [46-48]. In fact, although the limiting grain sizes may be different for ECAP and HPT, steps that eventually lead to these limiting grain sizes are the same. Such a power law relation is also in accordance with previous experimental findings [38].…”
Section: Resultsmentioning
confidence: 99%
“…8c also shows the fine intermetallics in Alloy 3. It is also observed that the intermetallics are extremely refined by the fast cooling in the high Fe and Si containing alloys (Alloy 2 and Alloy 3) [33].…”
Section: Optical Micrographsmentioning
confidence: 95%